2000
DOI: 10.1038/73957
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of stimulus selectivity of visual cortical cells in senescent rhesus monkeys

Abstract: Human visual function declines with age. Much of this decline is probably mediated by changes in the central visual pathways. We compared the stimulus selectivity of cells in primary visual cortex (striate cortex or V1) in young adult and very old macaque monkeys using single-neuron in vivo electrophysiology. Our results provide evidence for a significant degradation of orientation and direction selectivity in senescent animals. The decreased selectivity of cells in old animals was accompanied by increased res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
274
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(305 citation statements)
references
References 43 publications
29
274
2
Order By: Relevance
“…A related possibility is that compromised sensory processing is likely to result in decreased selectivity but not necessarily decreased activity. This effect has been observed in the primary visual cortex in aging monkeys (Schmolesky et al 2000). Degraded selectivity (specification of cell response) in these studies was accompanied by increased cell excitability and increased spontaneous activity.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…A related possibility is that compromised sensory processing is likely to result in decreased selectivity but not necessarily decreased activity. This effect has been observed in the primary visual cortex in aging monkeys (Schmolesky et al 2000). Degraded selectivity (specification of cell response) in these studies was accompanied by increased cell excitability and increased spontaneous activity.…”
supporting
confidence: 64%
“…A number of studies have suggested that there are age-related decreases in attention modulated neural specificity -most commonly observed as a decreased efficiency in the inhibition of unattended or less relevant information. Single cell recordings in senescent monkeys have shown significant reduction in selectivity of neurons in primary visual cortex that may reflect degradation of cortical inhibitory processes (Schmolesky et al 2000). In humans, scalp recorded event-related potential (ERP) studies have reported age-related changes in the amplitude, latency and topographic distribution of brain electrical responses, some of which are consistent with a decreased ability to selectively filter incoming information (review: Polich 1996).…”
mentioning
confidence: 99%
“…Previous studies dealing with age-related changes in the mammalian visual system have concluded that these are primarily cortical in nature (5,(34)(35)(36). Moreover, these studies emphasized the debilitating effects of the age-related changes, in particular the loss of orientation selectivity by cortical neurons, which appears to reflect a decrease in GABA-dependent neural communication (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Leventhal and colleagues (26,30) in normal aging monkeys reports physiological evidence of age-related changes in microcolumnar function including disruption of orientation selectivity, a property of the microcolumn in visual cortex. These changes may reflect a functional disruption of the microcolumn in normal aging, perhaps due to factors similar to those cited above that lead to subtle neuron displacements of sufficient magnitude to produce our observed change in S. It is important to note that the age-related decrease in S occurs in layer III of area 46 because the pyramidal cells of this layer give rise to ipsilateral and contralateral cortico-cortical connections.…”
Section: Mechanisms Of Change In Microcolumnarmentioning
confidence: 99%